Sexual conflict and deception in poison frogs. Issue 1 (1st February 2014) - Summers, Kyle
Abstract: I review evidence that females deceive males in the context of sexual selection and sexual conflict in the green poison frog, Dendrobates auratus . In this species, males mate polygynously when they have the opportunity, but polygyny imposes a cost on female reproductive success. Some females attempt to guard their mates when those males are approached by other females. This behavior involves both aggression toward other females and active "pseudo-courtship" of the male. This courtship is hypothesized to be a deceptive signal that functions to prevent the male from mating with other females. Observational and comparative evidence is presented in support of the predictions of this hypothesis. This form of deception is compared to similar behaviors that occur in other species, and the possibility that other forms of deception occur in poison frogs is discussed.